Sharpening emitter localization in front of a tuned mirror. Issue 1 (December 2018) - Heil, Hannah; Schreiber, Benjamin; Götz, Ralph; Emmerling, Monika; Dabauvalle, Marie-Christine; Krohne, Georg; Höfling, Sven; Kamp, Martin; Sauer, Markus; Heinze, Katrin
Abstract Single-molecule localization microscopy (SMLM) aims for maximized precision and a high signal-to-noise ratio1 . Both features can be provided by placing the emitter in front of a metal-dielectric nanocoating that acts as a tuned mirror2–4. Here, we demonstrate that a higher photon yield at a lower background on biocompatible metal-dielectric nanocoatings substantially improves SMLM performance and increases the localization precision by up to a factor of two. The resolution improvement relies solely on easy-to-fabricate nanocoatings on standard glass coverslips and is spectrally and spatially tunable by the layer design and wavelength, as experimentally demonstrated for dual-color SMLM in cells.